The inclusion of the performance sensitive debt in an emerging Economy – COLOMBIA (2016)
Execituve Summary. Introduction. The virtues of the inclusión of the Performance Sensitive Debt contract in the financing market. The Performance Sensitive Debt in the real sector. Colombia’s business sector. Conclusions. Bibliography. Graphics. Tables.